Sarcopenia as an independent predictor of the surgical outcomes of patients with inflammatory bowel disease: a meta-analysis - Erős, Adrienn (Surg Today, 2019)
Patients with inflammatory bowel disease (IBD) are at risk of sarcopenia, which is associated with poor clinical outcomes. We conducted this study to assess whether sarcopenia predicts the need for surgery and postoperative complications in patients with IBD. We performed a systematic search of four electronic databases, last updated in March, 2019. Data from studies comparing rates of surgery and postoperative complications in sarcopenic IBD patients versus non-sarcopenic IBD patients were pooled with the random-effects models. We calculated the odds ratios (OR) with a 95% confidence interval (CI). Ten studies with a collective total of 885 IBD patients were included in our meta-analysis. Although the analysis of raw data did not reveal significant differences between the two groups with respect to the rate of surgery and postoperative complications (OR = 1.826; 95% CI 0.913–3.654; p = 0.089 and OR = 3.265; 95% CI 0.575–18.557; p = 0.182, respectively), the analysis of adjusted data identified sarcopenia as an independent predictor for both of the undesirable outcomes (OR = 2.655; 95% CI 1.121–6.336; p = 0.027 and OR = 6.097; 95% CI 1.756–21.175; p = 0.004, respectively). Thus, early detection of sarcopenia in patients with IBD is important to prevent undesirable outcomes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00595-019-01893-8) contains supplementary material, which is available to authorized users.